2022
DOI: 10.3390/cells11152460
|View full text |Cite
|
Sign up to set email alerts
|

Static Magnetic Fields Regulate T-Type Calcium Ion Channels and Mediate Mesenchymal Stem Cells Proliferation

Abstract: The static magnetic fields (SMFs) impact on biological systems, induce a variety of biological responses, and have been applied to the clinical treatment of diseases. However, the underlying mechanisms remain largely unclear. In this report, by using human mesenchymal stem cells (MSCs) as a model, we investigated the biological effect of SMFs at a molecular and cellular level. We showed that SMF exposure promotes MSC proliferation and activates the expression of transcriptional factors such as FOS (Fos Proto-O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Based on our results, we hypothesized that magnetic stimulation disrupted the arrangement of cellular membranes, influencing cellular adhesion and attachment and, as a result, increasing the secretion of osteogenesis-related markers. Magnetic stimulation has also been reported to regulate calcium regulation and secretion, thereby activating several downstream intercellular signaling pathways for osteogenesis [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on our results, we hypothesized that magnetic stimulation disrupted the arrangement of cellular membranes, influencing cellular adhesion and attachment and, as a result, increasing the secretion of osteogenesis-related markers. Magnetic stimulation has also been reported to regulate calcium regulation and secretion, thereby activating several downstream intercellular signaling pathways for osteogenesis [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, it is reported that a moderate-intensity (40 ​mT) SMF resulted in histological improvement of rabbit cartilage extracellular matrix [ 35 ], and SMF (600 ​mT) exposure for 72 ​h stimulated the growth of human chondrocytes in vitro [ 34 ]. SMF (140 ​mT) regulated T-type calcium channels and mediated MSC proliferation through the MAPK signaling pathway [ 11 ], while SMF (280 ​mT) improved chondrogenesis and proliferation of mandibular bone marrow mesenchymal stem cells (MBMSCs) in the MBMSC/mandibular condylar chondrocyte coculture system [ 8 ]. The present study revealed that SMF reduced articular cartilage destruction.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the cost, adverse effects, and potential risks of drugs or surgical operations, non-invasive and handy SMF is potentially considered a physical therapeutic option [ 8 , 9 ]. Preclinical studies have shown that SMF can promote the proliferation, migration, adhesion, and differentiation of mesenchymal stem cells (MSCs) and improve cartilage defects [ 10 , 11 ]. However, the role of MSCs migration and the mechanism of SMF-driven chondrogenesis of osteoarthritic cartilage are yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…This study aims to investigate the role of ion channels in cultured neurons' response to DMFs. Voltage‐dependent ion channels, such as the T‐type calcium channel, are potential candidates for sensing magnetic fields [18]. These channels play a role in mediating cell proliferation and gene expression through signaling pathways like Mitogen‐Activated Protein Kinase.…”
Section: Discussionmentioning
confidence: 99%